If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + -3n) = 27 + 4n (1 * -7 + -3n * -7) = 27 + 4n (-7 + 21n) = 27 + 4n Solving -7 + 21n = 27 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -7 + 21n + -4n = 27 + 4n + -4n Combine like terms: 21n + -4n = 17n -7 + 17n = 27 + 4n + -4n Combine like terms: 4n + -4n = 0 -7 + 17n = 27 + 0 -7 + 17n = 27 Add '7' to each side of the equation. -7 + 7 + 17n = 27 + 7 Combine like terms: -7 + 7 = 0 0 + 17n = 27 + 7 17n = 27 + 7 Combine like terms: 27 + 7 = 34 17n = 34 Divide each side by '17'. n = 2 Simplifying n = 2
| 8r-72=5r+25 | | -2-6(m-3)=-19-m | | 9+-7k=2+-77 | | 25x^2-1000x+100=0 | | .50-66.6x=.25 | | 3x^2-16x=-4x^2-3x-6 | | 5-7r=-5(r-3) | | 2.5+2n=2.75 | | x^2-40x+4=0 | | 10-0.5=14 | | 8(3x-19)=15x+73 | | 3x+4-6x=-x+8 | | -3v+8=22 | | 15=3(2q-1) | | 13+4a=-3 | | 8x-7=-3(1-4x)-8x | | 10x^2-1015x+100=0 | | 4x+22=-2(14+3x) | | 2.7+6s+1.8=6.5 | | 3[2-4(2x-1)]=-10x-10 | | x^2=x-32 | | 5(4+8x)+6=26+8x | | 6-2(5x-8)=-2(2x+1) | | 6x+9=9x-16 | | -4x-10=-25+x | | 0.4e-0.04+0.4e=2.66 | | 16x^5-2x^2=0 | | 4-x=-3x-8 | | .75z=-24 | | (2x^2)-(9)-(6x)=0 | | 60t=40t-20 | | .75x-2=-11 |